2020
DOI: 10.3390/jcm9061887
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA Expression Profile in the Airways Is Altered during Pulmonary Exacerbation in Children with Cystic Fibrosis—A Preliminary Report

Abstract: MicroRNAs are small non-coding RNAs that regulate immune response and inflammation. We assumed that miRNAs may be involved in the immune response during cystic fibrosis pulmonary exacerbations (CFPE) and that altered expression profile in the airways and blood may underlie clinical outcomes in CF pediatric patients. Methods: We included 30 pediatric patients diagnosed with cystic fibrosis. The biologic material (blood, sputum, exhaled breath condensate) was collected during pulmonary exacerbation and in stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This miRNA was not selected by the authors for further validation by qPCR but it would be interesting to see if its expression was significantly altered in a larger cohort, including equal numbers of male/female samples in both the CF and non-CF groups, and if there are any correlations with clinical parameters. A recent study by Stachowiak et al (2020) reported a number of miRNAs from airway samples to show correlation with CF pulmonary exacerbation parameters, one of which was an X-linked miRNA, miR-223-3p. Increased levels of miR-223-3p were found in exhaled breath condensate and sputum during pulmonary exacerbation with concurrent Aspergillus infection.…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA was not selected by the authors for further validation by qPCR but it would be interesting to see if its expression was significantly altered in a larger cohort, including equal numbers of male/female samples in both the CF and non-CF groups, and if there are any correlations with clinical parameters. A recent study by Stachowiak et al (2020) reported a number of miRNAs from airway samples to show correlation with CF pulmonary exacerbation parameters, one of which was an X-linked miRNA, miR-223-3p. Increased levels of miR-223-3p were found in exhaled breath condensate and sputum during pulmonary exacerbation with concurrent Aspergillus infection.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-486-5p expression is decreased in the serum samples and lung tissues of patients with silicosis and idiopathic pulmonary brosis [18]. MiR-486-5p targets SMAD2, a crucial mediator of pulmonary brosis [19] and decreases pulmonary exacerbation in patients [20]. Growing evidence has indicated that miR-486-5p regulates in ammation and brosis in lung tissues [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…The low yield of miRNA from the EBC is a major obstacle, which was successfully overcome in 2 studies using the NGS technology. 22 , 24 Also, its potential for discovering previously unidentified miRNAs 21 would make it more suitable for the purposes of the project we are about to launch on detecting new molecular signatures as early biomarkers of asbestos-related health effects. Based on such assumptions, we conducted a preliminary test on male volunteers to compare of the EBC miRNA profile in the EBC to that in the plasma using 2 sequencing platforms, different in terms of cost and performance.…”
Section: Introductionmentioning
confidence: 99%